2023
DOI: 10.3390/s23041778
|View full text |Cite
|
Sign up to set email alerts
|

Design and Experiments of a Real-Time Bale Density Monitoring System Based on Dynamic Weighing

Abstract: Bale density is one of the main performance indicators to measure the quality of baler operation. In this study, a real-time baler bale density monitoring system was designed for the problem of difficult real-time measurement of bale density on round balers. Firstly, a weighing calculation model for the rolling and sliding stage of the bale was established, and the dynamic characteristics during the contact between the bale and the inclined surface were analyzed based on ADAMS dynamics simulation. Then, a real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…After integrating the information from the various components, the grain yield monitoring system was run in an interface developed in the Keil MDK development environment [20,21]. The data processing program of the system was divided into three parts: the first part was the monitoring program, responsible for the system's power-on selfexperiment, initialization, and similar functions.…”
Section: Software Design Of Grain Yield Monitoring Systemmentioning
confidence: 99%
“…After integrating the information from the various components, the grain yield monitoring system was run in an interface developed in the Keil MDK development environment [20,21]. The data processing program of the system was divided into three parts: the first part was the monitoring program, responsible for the system's power-on selfexperiment, initialization, and similar functions.…”
Section: Software Design Of Grain Yield Monitoring Systemmentioning
confidence: 99%
“…Some scholars used the method of laying radio resistance strain gauges on steel rolls and ANSYS simulation to study the change rule of radial force in the process of roll compression and established the compression model and stress relaxation model [17]. Yin et al [18] found a weighing calculation model for the rolling and sliding phases of the hay bale in response to the problem that the density of the rolled bale in the round bale machine is difficult to measure in real time. A monitoring system based on slant contact pressure, attitude angle measurement and the hydraulic cylinder was constructed, and the accuracy of the weighing model was verified.…”
Section: Introductionmentioning
confidence: 99%
“…There are known solutions that, based on the pressure measurement in the hydraulic system, draw conclusions about the density of the bales being pressed. It is necessary to filter the signal from pressure sensors, because it is characterized by large fluctuations [ 17 ]. Automation of the net feeding process, based on the analysis of the bale density signal, allows an increase in productivity of 14%, by controlling the pressure in the baler’s hydraulic system.…”
Section: Introductionmentioning
confidence: 99%
“…The bale weight measurement is based on the coupling of mechanisms with force sensors on the receiver, that transfers bales from the pressing chamber [ 17 ]. Systems of applying additives, supporting the creation of high-quality fodder in balers and baler-wrappers, in the form of nozzles dosing ensilage agents mounted above the pick-up of the machine, are also observed [ 19 ].…”
Section: Introductionmentioning
confidence: 99%